A study of the external finger fixator to correct flexion deformity - Rahman, Herman Shah; Abu Osman, Noor Azuan; Yahud, S.; Tunku Yahya, T.S.; Ng, Eng Seng (Elsevier, 2007)
Severe fixed flexion deformities at the fingers are common injuries that can lead to pain and stiffness when treated improperly. The damage varies from a sprain of the collateral ligaments to an all-round comminuted fracture-dislocation. The flexion deformities occur because of a variety of issues including fractures (broken bones), burns, tissue expansion, facial contracture and finger joint dislocation [1]. With conventional splints it is difficult to apply an effective torque without causing pain and inflammation due to pressure on the skin. The objective of the study is to develop a new design for external finger fixator to correct severe fixed flexion deformity. Siow et al. (1999) conducted a clinical trial on three patients by using mini external fixator where each of them had severe fixed flexion of deformity. The device was applied up to 44 days and post-operative observation showed that the effected finger can extend up to 75% from the initial range of motion [2]. The use of this external fixator for correction of rigid soft tissue deformities of the hand has proved that it is not only feasible, but works well.